Play Therapy For Children Victims Of The Aceh Tamiang Flood - Muhammad Arif Syailendra; Wan Chalidaziah (At Turots: Jurnal Pendidikan Islam, 2026)
The main problem in this context is that the psychosocial impact on flood victims has not been optimally handled, even though the number affected is quite large. Interventions still focus on physical needs, while children's emotional disorders, such as fear, anxiety, and withdrawal, have not been systematically and sustainably addressed. This study aims to analyze the implementation of clown-based play therapy and drawing activities as a recovery approach for children affected by the Aceh Tamiang flood in 2025 and analyze what obstacles occur during the implementation process. The research used a qualitative method with a case study design involving 30 children, supported by one clown as the main facilitator, one field coordinator, and three drawing activity facilitators. Data was collected through semi-structured interviews, participant observations, and documentation, then analyzed using an interactive model that included data reduction, data presentation, and conclusion drawn. The validity of the data is strengthened through source triangulation.  The results of the study show that the implementation  of clown-based play therapy and drawing for children affected by the Aceh Tamiang flood in 2025 is carried out in a structured manner through the preparation, implementation, and evaluation stages. The intervention was designed contextually by utilizing simple media that was appropriate to the conditions of the evacuation. However, the implementation faced the main obstacles in the form of differences in the readiness of participants, limited time of 1-2 hours, a less conducive environment, and limited facilitators and media. In conclusion, the success of play therapy in the context of a disaster depends not only on the methods used, but also on the preparedness of the participants, environmental conditions, and the availability of resources. Therefore, these kinds of interventions require adaptive planning and ongoing support in order to be implemented more effectively.